Biomass production, arbuscular mycorrhizae and soil plant-available P under water stress in native perennial grasses - Busso, Carlos Alberto; Bolletta, Andrea Ivana (CRC Press-Taylor & Francis, 2022)
Precipitation determines vegetation type and species relative composition in plant communities [1]; in addition, it is a primary variable affecting soil water storage and availability. This availability is the most important factor which affects plant distribution, growth and survival in rangelands throughout the world [2]. Plant productivity can be reduced in these rangelands because of the negative effects of water stress on plant growth [2].